Implementation Execution Decision Court Industrial Relations Bandung Dispute over Termination of Employment Through Bankruptcy - Sahatatua , Richart; Syahrul Ansari , Teuku; Ketut Astawa , I; Maman Suherman, Ade; Asihany Pakpahan , Dessy; of Donri Tinambunan , Revelation; Budi Santoso, Imam; Noor, Aslan; Jaya Pakpahan , Edison; Florida Elyzabeth, Eka; Setiady, Try (IJBLE Scientific Publications Community Inc., 2024)
Study This discusses the implementation execution decision of the Court Industrial Relations (PHI) Bandung-related dispute Termination Connection Work (PHK) through mechanism bankruptcy. PHI decisions often face​ constraints in implementation, especially in unsolved layoff disputes that can quickly be executed. Bankruptcy is one of the instruments used​ to ensure workers' rights are fulfilled when the Company has financial trouble. Research This is to study how the bankruptcy process can be used as a road alternative for finishing layoff disputes and challenging the law's implementation. The research uses a legal normative approach supported by case PHI Bandung decision studies. Research results show that although Bankruptcy can become a practical solution, it requires synergy between the court and curator so execution can run optimally.